Control of cell death and mitochondrial fission by ERK1/2 MAP kinase signalling. (18th June 2017) - Cook, Simon J.; Stuart, Kate; Gilley, Rebecca; Sale, Matthew J.
Abstract : The ERK1/2 signalling pathway is best known for its role in connecting activated growth factor receptors to changes in gene expression due to activated ERK1/2 entering the nucleus and phosphorylating transcription factors. However, active ERK1/2 also translocate to a variety of other organelles including the endoplasmic reticulum, endosomes, golgi and mitochondria to access specific substrates and influence cell physiology. In this article, we review two aspects of ERK1/2 signalling at the mitochondria that are involved in regulating cell fate decisions. First, we describe the prominent role of ERK1/2 in controlling the BCL2‐regulated, cell‐intrinsic apoptotic pathway. In most cases ERK1/2 signalling promotes cell survival by activating prosurvival BCL2 proteins (BCL2, BCL‐xL and MCL1) and repressing prodeath proteins (BAD, BIM, BMF and PUMA). This prosurvival signalling is co‐opted by oncogenes to confer cancer cell‐specific survival advantages and we describe how this information has been used to develop new drug combinations. However, ERK1/2 can also drive the expression of the prodeath protein NOXA to control 'autophagy or apoptosis' decisions during nutrient starvation. We also describe recent studies demonstrating a link between ERK1/2 signalling, DRP1 and the mitochondrial fission machinery and how this may influence metabolic reprogramming during tumorigenesis and stem cell reprogramming. With advances in subcellular proteomics it is likely that new roles for ERK1/2, and new substrates, remain to be discovered at the mitochondria and other organelles. Abstract : ERK1/2 signalling is best known for regulating gene expression in the nucleus. However, ERK1/2 also exerts profound effects on cell physiology by acting at the mitochondria to inhibit apoptosis and to promote mitochondrial fission. Mitochondrial ERK1/2 signalling is important in stem cell reprogramming and in cancer, where certain tumour cells become addicted to ERK1/2‐dependent survival signals, providing an opportunity for targeted therapy.